REGIONAL INEQUALITY IN JAVA: A SYSTEMATIC REVIEW OF THE LITERATURE ON INEQUALITY INDICES AND DETERMINANTS OF DEVELOPMENT - Muhammad Arsy Quraisyhab; Anna Yulianita; Sukanto (ITB AAS Indonesia Surakarta, 2025)
This study aims to systematically analyze the literature related to regional inequality in six provinces in Java. The study focused on the use of five inequality indicators: Gini Coefficient, Atkinson Index, Theil Index, Robin Hood Index, and Williamson Index. This study also explores the relationship between inequality and development factors such as Gross Regional Domestic Product (GDP), Per Capita Income (GDP), and Human Development Index (HDI). Using the Systematic Literature Review (SLR) approach which refers to the PRISMA protocol, as many as 25 articles from 2010–2024 were analyzed thematically. The findings show that increasing HDI significantly reduces inequality, while increasing PDRPC without fair distribution actually widens the gap. This article contributes to formulating regional development policy recommendations based on spatial justice and quality of life. Keywords: Regional Inequality, IPM, PDRPC, PDRB, Inequality Index, Systematic Literature Review